2017
DOI: 10.3389/fnmol.2017.00161
|View full text |Cite
|
Sign up to set email alerts
|

Increasing N-acetylaspartate in the Brain during Postnatal Myelination Does Not Cause the CNS Pathologies of Canavan Disease

Abstract: Canavan disease is caused by mutations in the gene encoding aspartoacylase (ASPA), a deacetylase that catabolizes N-acetylaspartate (NAA). The precise involvement of elevated NAA in the pathogenesis of Canavan disease is an ongoing debate. In the present study, we tested the effects of elevated NAA in the brain during postnatal development. Mice were administered high doses of the hydrophobic methyl ester of NAA (M-NAA) twice daily starting on day 7 after birth. This treatment increased NAA levels in the brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 83 publications
1
13
0
Order By: Relevance
“…Consequently, the increased overall NAA levels in ThyNAT brain extracts reflect increased extracellular or intra-neuronal concentrations that are not toxic per se and do not trigger a substantial alteration in principal osmolytes. This is supported by recent findings that extracellular elevation of NAA does not cause vacuolating histopathology [ 4 ]. While the aetiology is multifactorial, based on our data, we hypothesize that the CD pathology is triggered by oligodendroglial intolerance to supra-physiological NAA concentrations.…”
Section: Discussionsupporting
confidence: 83%
“…Consequently, the increased overall NAA levels in ThyNAT brain extracts reflect increased extracellular or intra-neuronal concentrations that are not toxic per se and do not trigger a substantial alteration in principal osmolytes. This is supported by recent findings that extracellular elevation of NAA does not cause vacuolating histopathology [ 4 ]. While the aetiology is multifactorial, based on our data, we hypothesize that the CD pathology is triggered by oligodendroglial intolerance to supra-physiological NAA concentrations.…”
Section: Discussionsupporting
confidence: 83%
“…ASPA is broadly expressed in various tissues but plays an essential role in the degradation of N-acetylaspartate (NAA), one of the most abundant metabolites in the brain (Rigotti et al, 2011;Tallan, 1957). If deficient, NAA abnormally builds up in the CNS, leading to NAA acidemia and aciduria as well as a broad range of deleterious effects such as dysmyelination and spongiform degeneration in the CNS (Appu et al, 2017;Janson et al, 2006). During life, patients commonly present with head lag, macrocephaly, hypotonia, ataxia, inadequate visual tracking, epilepsy, and intellectual disabilities (Hoshino and Kubota, 2014), and many patients die before adolescence.…”
Section: Lysosomal Storage Diseasesmentioning
confidence: 99%
“…Two recent studies found that elevating [NAA B ] in Aspa +/+ mice, either by oral administration of NAA-methyl ester 28 or by engineering neuronal transgenic overexpression of Nat8l, 26 was not sufficient to cause brain vacuolation. These results suggest that both aspartoacylase deficiency and elevated [NAA B ] are necessary to elicit spongiform leukodystrophy in Canavan disease.…”
Section: Discussionmentioning
confidence: 99%